First description of deep-sea polyclad flatworms from the North Pacific: Anocellidus n. gen. profundus n. sp. (Anocellidae, n. fam.) and Oligocladus voightae n. sp. (Euryleptidae) - Quiroga, Sigmer Y.; Bolaños, D. Marcela; Litvaitis, Marian K. (Zootaxa, 2006)
Two deep-sea polyclad species are described. Both species were found in association with wood-boring bivalves on oak and fir wood blocks that had been deployed on heavy sediment in the Cascadia Basin and Escanaba Trough in the North Pacific Ocean. Anocellidus profundus n. gen. n. sp. warrants erection of Anocellidae, n. fam. because of the unique position and orientation of the male copulatory apparatus. A. profundus lacks eyes but has long, nuchal tentacles and a ventral, arrowhead-shaped organ of putative sensory function. The male copulatory apparatus is located posterior to the male gonopore and is directed anteriorly. Highly muscularized spermiducal bulbs are present, a prostatic vesicle is lacking. A large Lang’s vesicle characterizes the female reproductive system. Oligocladus voightae n. sp. is defined by the presence of a mouth located anterior to the brain. Few and minute tentacular eyes are present. The seminal vesicle is connected to an auxiliary sperm storage vesicle, and a posterior anal pore is present in the main median branch of the intestine. All type material is deposited at the Field Museum of Natural History, Chicago, Illinois, USA.